'Walking the tightrope': The role of peer support workers in facilitating consumers' participation in decision‐making. (9th May 2018) - Cleary, Michelle; Raeburn, Toby; Escott, Phil; West, Sancia; Lopez, Violeta
Abstract: In adult mental health services, the participation of consumers is essential. The aim of this study was to explore the challenges faced by peer support workers when involving mental health consumers in decision‐making about their care and the strategies they employed to overcome these challenges so as to improve mental health consumers' participation in decision‐making and recovery. Semi‐structured individual interviews were conducted with six peer support workers currently employed in psychiatric hospitals and/or community mental health systems. Thematic analysis identified challenges related to role definition, power imbalance, doctor‐centric medical approaches to care, and lack of resources. Strategies to overcome these challenges that were reported, included the following: facilitating meaningful involvement for service users, appropriate use of the lived experience, building relationships and communication, promoting rights and advocacy, and promoting professionalism of peer support workers (PSWs). Nursing staff need ongoing support and education to understand and value the varied roles of PSWs and thereby empower PSWs to engage in enhancing consumer decision‐making. The roles of the PSWs should be viewed as complementary, and greater appreciation and understanding of roles would better support recovery‐oriented care.